2023
DOI: 10.1002/clc.24178
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and feasibility of vein of Marshall ethanol infusion during persistent atrial fibrillation ablation: A systematic review and meta‐analysis

Wei‐Li Ge,
Tao Li,
Yi‐Fei Lu
et al.

Abstract: BackgroundCatheter ablation (CA) is currently used to treat persistent atrial fibrillation (PeAF). However, its effectiveness is limited. This study aimed to estimate the effectiveness of the vein of Marshall absolute ethanol injection (VOM‐EI) for PeAF ablation.HypothesisAdjunctive vein of Marshall ethanol injection (VOM‐EI) strategies are more effective than conventional catheter ablation (CA) and have similar safety outcomes.MethodsWe extensively searched the literature for studies evaluating the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Additionally, a 2020 study of 103 patients presenting with perimetral flutter post prior AF ablation demonstrated higher rates of acute mitral isthmus block with a reduction in the duration of RF ablation needed to achieve AT termination and block, further translating into less recurrence on midterm follow-up [56]. These findings were echoed by a 2023 meta-analysis of 9 studies, including 2508 patients that compared adjunct VoM to catheter ablation alone, and reported significantly higher rates of acute bidirectional block at the mitral isthmus (p = 0.0007) with lower rates of recurrent AT and AF post blanking period (p = 0.008) [17].…”
Section: Mitral Isthmus Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a 2020 study of 103 patients presenting with perimetral flutter post prior AF ablation demonstrated higher rates of acute mitral isthmus block with a reduction in the duration of RF ablation needed to achieve AT termination and block, further translating into less recurrence on midterm follow-up [56]. These findings were echoed by a 2023 meta-analysis of 9 studies, including 2508 patients that compared adjunct VoM to catheter ablation alone, and reported significantly higher rates of acute bidirectional block at the mitral isthmus (p = 0.0007) with lower rates of recurrent AT and AF post blanking period (p = 0.008) [17].…”
Section: Mitral Isthmus Ablationmentioning
confidence: 99%
“…The Vein of Marshall (VoM) is an embryological remnant of the superior vena cava that has been has been implicated as a potential source of AF triggers and is known to harbour sympathetic and parasympathetic nerve fibres that play a significant role in the pathogenesis and maintenance of AF [15,16]. Ethanol infusion of this vein during AF ablation may eliminate these triggers and may facilitate mitral isthmus block, given its anatomic location at the mitral isthmus [17], potentially overcoming one of the main challenges with adjunct linear ablation. Promising results have been demonstrated in the Venus randomised trial of persistent AF ablation with significantly higher arrhythmiafree survival demonstrated in those receiving concomitant VoM 'ethanolisation' [18].…”
Section: Introductionmentioning
confidence: 99%
“…While the evidence regarding the impact of adjuvant EI-VOM on AF's clinical outcome has not been robustly established by several multiple prospective randomized studies to date, several meta-analyses have been presented [44][45][46][47]. He Z et al synthesized a total of 10 studies [20,21,26,33,34,42,[48][49][50][51] involving 1322 patients, of which five studies (923 patients) investigated the efficacy of EI-VOM combined with CA versus CA alone in AF patients [45].…”
Section: Impact Of Ei-vom On Af Outcomementioning
confidence: 99%
“…Despite the analysis not reaching significance in terms of the recurrent rate of AF and/or AT between the EI-VOM combined with CA group and CA alone group (RR: 0.68, 95% CI: 0.45-1.02, p = 0.06), focusing on the persistent AF population [33,34,42] revealed a significantly lower recurrence of AF and/or AT in the EI-VOM combined with CA group compared to the CA alone group (RR: 0.58, 95% CI: 0.35-0.96, p = 0.04). In a meta-analysis by Ge W et al [46], a comprehensive review of nine studies [15,20,22,25,34,42,48,52,53], encompassing a staggering 2508 patients experiencing AF, was meticulously undertaken. Among this cohort, 1028 patients underwent EI-VOM + CA, while 1605 underwent CA alone.…”
Section: Impact Of Ei-vom On Af Outcomementioning
confidence: 99%